Kualitas Tulang Mandibula pada Wanita Pasca Menopause - Lindawati Khusdany; Gimawati Mulyono; Evy Savitri Baskara; Maryantoro Oemardi; Tri Budi W. Rajardjo (Faculty of Dentistry, Universitas Indonesia, 2015)
The need to use a dental prostheses in women increases with age. Low estrogen level is characteristic in post menopausal women, they are therefore more prone to severe osteoporosis than women at other ages. Osteoporosis is a disease characterized by low bone mass and the developemtn of fractures as a direct result of the low bone mass. In this preliminary study, five women aged between 53 - 62 years were observed. Bone density was determined by means of bone densitometry Lunar DPX-L and panoramic radiographs. The results showed that the tendency of osteopenie (L1, L2 and L3) was associated with the increase of age, while using panoramic radiography there were no mandible radiolucency among those under 60 years. In addition, based on densitometry and panoramic radiography, osteoporos was detected in subjects over 60 years of age. It can be concluded that the quality of the mandible in this study was relatively low among those over 60 years old.